2015
DOI: 10.1021/acsnano.5b01329
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Tolerant Aligned Dipoles within Two-Dimensional Plastic Lattices

Abstract: Carboranethiol molecules self-assemble into upright molecular monolayers on Au{111} with aligned dipoles in two dimensions. The positions and offsets of each molecule's geometric apex and local dipole moment are measured and correlated with sub-Ångström precision. Juxtaposing simultaneously acquired images, we observe monodirectional offsets between the molecular apexes and dipole extrema. We determine dipole orientations using efficient new image analysis techniques and find aligned dipoles to be highly defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(76 citation statements)
references
References 72 publications
3
72
0
1
Order By: Relevance
“…Hence, SAMs of CTs and their derivatives have attracted increasing interest in recent years. [47][48][49][50][51][52][53][54][55][56][57][58] Recently, Lübben and coworkers have demonstrated that by using pure and mixed SAMs of two carborane dithiol isomers [1,2-(HS 2 )-1,2-C 2 B 10 H 10 and 9,12-(HS 2 )-1,2-C 2 B 10 H 10 ] with opposite dipole moments, the surface potential of silver surfaces could be tuned. Weiss et al, on the other hand, used two CT isomers [1-HS-1,7-C 2 B 10 H 11 (M1) and 9-HS-1,7-C 2 B 10 H 11 (M9), see figure 1 for naming of CT isomers] and were able to tune the gold work function over a range of 0.8 eV by preparing mixed SAMs of these two isomers in different ratios.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, SAMs of CTs and their derivatives have attracted increasing interest in recent years. [47][48][49][50][51][52][53][54][55][56][57][58] Recently, Lübben and coworkers have demonstrated that by using pure and mixed SAMs of two carborane dithiol isomers [1,2-(HS 2 )-1,2-C 2 B 10 H 10 and 9,12-(HS 2 )-1,2-C 2 B 10 H 10 ] with opposite dipole moments, the surface potential of silver surfaces could be tuned. Weiss et al, on the other hand, used two CT isomers [1-HS-1,7-C 2 B 10 H 11 (M1) and 9-HS-1,7-C 2 B 10 H 11 (M9), see figure 1 for naming of CT isomers] and were able to tune the gold work function over a range of 0.8 eV by preparing mixed SAMs of these two isomers in different ratios.…”
Section: Introductionmentioning
confidence: 99%
“…Hence Weiss et al proposed that the head-to-tail orientation of the dipoles of the M1 molecules could yield a more favorable adsorption when compared with M9. In addition, very recently they showed that dipole-dipole interactions to be highly defect tolerant based on STM measurements 57…”
Section: Introductionmentioning
confidence: 99%
“…Here, the goal is to isolate defects and artifacts from interfering with the regular modes. We note that these image defects and artifacts can be the result of important physical structures [8,36,67,68].…”
Section: Artifact Indicator Functionmentioning
confidence: 95%
“…Nanoscale images such as these are a useful testbed since data are often oversampled relative to the smallest observable features, atoms and molecular parts. Also, segmentation in one imaging modality can be used to guide segmentation or data acquisition in a complementary imaging mode [3,8,36,51,67].…”
Section: Segmentation Of Peptide β-Sheetsmentioning
confidence: 99%
See 1 more Smart Citation